PENGARUH MOTIVASI TERHADAP KEPATUHAN DIET PASIEN HIPERTENSI USIA PRODUKTIF DI PUSKESMAS KRIAN SIDOARJO - Inike Kusuma Dewi; Eka Diah Kartiningrum; Mohammad Yusuf Alamudi (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2025)
The incidence of hypertension in the productive age group in Indonesia is increasing. Treatment of hypertension in all age groups is generally carried out over a long period of time and is sustainable in addition to a regular diet and physical activity program. Many factors affect patient compliance in undergoing a hypertension diet, including motivation. The purpose of the study was to analyze the effect of motivation on dietary compliance of hypertensive patients of productive age at the Krian Sidoarjo Health Center. This study used a cross sectional approach with a sample of 94 hypertensive patients of productive age (15-59 years) who visited the Krian Health Center. Samples were selected using simple random sampling technique. Data were collected using a questionnaire and then analyzed using the Logistic Regression test. The results showed that self-motivation, the most dominant was poor with a frequency of 56 with a percentage of 59.6%, and good at 38 with a percentage of 40.4%. Self-motivation proved to be the most significant factor affecting dietary adherence, with a p value of 0.000 and an OR value of 20.56. Self-motivation is a predictor in dietary adherence in patients with hypertension. The higher the motivation, the higher the patient's dietary adherence. Therefore, more effective interventions may need to combine increased self-motivation with more appropriate education and integrated support from various sources.